Effect of DON and ZEN and their metabolites DOM-1 and HZEN on B cell proliferation and antibody production - Pierron, Alix; Kleber, Alexandra; Mayer, Elisabeth; Gerner, Wilhelm (Frontiers in Immunology, 2024)
The mycotoxins deoxynivalenol (DON) and zearalenone (ZEN), produced by Fusarium fungi, are frequently found in the cereal-rich diet of pigs and can modulate the immune system. Some enzymes or bacteria present in the digestive tract can de-epoxydize DON to deepoxy-deoxynivalenol (DOM-1) and biotransform ZEN into hydrolyzed ZEN (HZEN). The effects of these metabolites on immune cells, particularly with respect to the vaccine responses, are poorly documented. The aim of this study was to address the impact of DON and ZEN and their respective derivatives, on proliferation, and antibody production of porcine B cells in vitro. Peripheral blood mononuclear cells (PBMCs), isolated from healthy pigs, were stimulated with the Toll-like receptor (TLR) 7/8-agonist Resiquimod (R848) or the TLR/1/2-agonist Pam3Cys-SKKKK in combination with DON [0.1-1.6 µM] or DOM-1 [1.6 µM and 16 µM] and ZEN [2.5-40 µM] or HZEN [40 µM]. A strong decrease in B-cell proliferation was observed at DON concentrations equal to or exceeding 0.8 µM and at ZEN concentrations equal to or exceeding 20 µM. Treatment with 1.6 µM DON or 40 µM ZEN led to almost a complete loss of live CD79α+ B cells. Moreover, CD21 expression of proliferating IgG+ and IgM+ B-cell subsets was decreased at DON concentrations equal to and exceeding 0.4 µM and at ZEN concentrations equal to or exceeding 10 µM. ELISpot assays revealed a decrease of IgG-secreting B cells at concentrations of and exceeding 0.4 µM and at ZEN concentrations equal to and exceeding 10 µM. ELISA assays showed a decrease of IgM, IgG, and IgA secretion at concentrations equal to or exceeding 0.4 µM DON. ZEN reduced IgM secretion at 20-40 µM (both R848 and Pam3Cys-SKKKK), IgG secretion at 40 µM (both R848 and Pam3Cys-SKKKK) and IgA secretion at 20-40 µM. Our in vitro experiments show that while DON and ZEN impair immunoglobulin production and B-cell proliferation, this effect is abrogated by HZEN and DOM-1.